(untitled) (Hoboken, NJ, 2003)
Focuses on the examination of physiological processes within the skeletal and muscular systems of the body, using animations, interactivity, and clinical correlations to enhance student understanding
Keywords: Kinesiology,Musculoskeletal system,Vận động học,Hệ cơ xương; Software,Software,Phần mềm máy tính,Phần mềm máy tính